Down-regulation of p38 mitogen-activated protein kinase activation and proinflammatory cytokine production by mitogen-activated protein kinase inhibitors in inflammatory bowel disease - Docena, Guillermo H. (2010)
Crohn's disease and ulcerative colitis are inflammatory bowel diseases (IBD) characterized by chronic relapsing mucosal inflammation. Tumour necrosis factor (TNF)-α, a known agonist of the mitogen-activated protein kinase (MAPK) pathway, is a key cytokine in this process. We aimed first to determine whether p38 MAPK is activated in IBD inflamed mucosa, and then studied the effect of four different p38α inhibitory compounds on MAPK phosphorylation and secretion of proinflammatory cytokines by IBD lamina propria mononuclear cells (LPMCs) and organ culture biopsies. In vivo phospho-p38α and p38α expression was evaluated by immunoblotting on intestinal biopsies from inflamed areas of patients affected by Crohn's disease and ulcerative colitis, and from normal mucosa of sex- and age-matched control subjects. Both mucosal biopsies and isolated LPMCs were incubated with four different p38α selective inhibitory drugs. TNF-α, interleukin (IL)-1β and IL-6 were measured in the organ and cell culture supernatants by enzyme-linked immunosorbent assay. We found higher levels of phospho-p38α in the inflamed mucosa of IBD patients in comparison to controls. All the p38α inhibitory drugs inhibited p38α phosphorylation and secretion of TNF-α, IL-1β and IL-6 from IBD LPMCs and biopsies. Activated p38α MAPK is up-regulated in the inflamed mucosa of patients with IBD. Additionally, all the p38α selective inhibitory drugs significantly down-regulated the activation of the MAPK pathway and the secretion of proinflammatory cytokines.